Self-lubricating anticoagulation surface coating as well as preparation method and application thereof
By preparing a self-lubricating anticoagulation coating on the surface of the blood pump material, the blood cell damage and thrombosis caused by traditional blood pump materials during the flow shearing process is solved, and better blood compatibility and anticoagulation performance are achieved.
Patent Information
- Application Number
- CN202411744147.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional blood pump materials lead to problems of blood cell damage, hemolysis and thrombosis during flow shearing, limiting the application range of blood pumps and increasing the risk to patients.
Using a self-lubricating anticoagulant surface coating, including a silicone oil-polydimethylsiloxane gel layer, is engaged on the substrate surface with a porous structure, the surface of the silicone oil-polydimethylsiloxane gel layer has a continuous silicone oil lubricating layer.
It significantly reduces the shear force during blood flow, reduces the collision and friction damage of blood cells, improves anticoagulant performance, prolongs the use time of blood in the extracorporeal circulatory system, and has antibacterial properties and self-healing properties.
Smart Images

Figure CN119564947A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of research and development of biomedical instruments and medical materials, and relates to a self-lubricating anti-coagulation surface coating and a preparation method and application thereof. Background Art
[0002] Improving the blood compatibility of membrane lung oxygenation (ECMO) instrument tubing and blood pump materials is the key to reducing complications during ECMO use and improving patient treatment outcomes. Traditional blood pump designs mainly reduce the damage to blood cells caused by flow shear by optimizing the mechanical structure, but this method cannot completely solve the hemolysis and thrombosis problems caused by blood cell collision and friction in the blood pump. These problems limit the scope of application of blood pumps and increase the risks to patients. Therefore, developing new materials to fundamentally improve the blood compatibility of blood pumps and tubing materials has become a hot topic and difficulty in current research.
[0003] At present, some surface modification technologies have been used to improve blood compatibility in membrane oxygenation materials used in clinical applications. For example, heparin coating, as a commonly used anticoagulant material, effectively reduces the risk of thrombosis by accelerating the rate at which antithrombin neutralizes active coagulation factors. However, heparin coating also has some shortcomings, such as high cost, susceptibility to mechanical wear and chemical corrosion, etc. In addition, hydrogel coatings have attracted widespread attention due to their versatility, biocompatibility and stimulus responsiveness. However, in practical applications, the synthesis process of hydrogel coatings may produce toxic substances and cause environmental pollution, and experimental verification in specific application areas (such as marine antifouling) is still insufficient. These problems limit the application of hydrogel coatings in ECMO instruments. Polyethylene oxide (PEO) coating, as a potential material choice, has certain biocompatibility, but due to the lack of true three-dimensional structural surface modification, it cannot mimic the self-lubricating function of the endothelium, resulting in poor anticoagulation, poor antibacterial properties and greater blood cell damage.
[0004] In order to overcome the shortcomings of existing materials and further improve the blood compatibility of membrane oxygenator pipelines and blood pumps, researchers are actively exploring new methods of modifying materials. Therefore, developing new coating materials with better anticoagulant, antiplatelet aggregation and antibacterial properties to reduce blood cell damage and inhibit inflammatory response has become the focus of current research. Summary of the invention
[0005] In order to solve the problem of damage to blood cells caused by flow shear in traditional nickel-titanium alloy blood pumps, reduce hemolysis and thrombosis caused by collision and friction damage of blood cells, and improve the blood compatibility of medical materials, the present invention provides a self-lubricating anti-coagulation surface coating and its preparation method and application.
[0006] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a self-lubricating anti-coagulation coating, comprising a silicone oil-polydimethylsiloxane gel layer, the silicone oil-polydimethylsiloxane gel layer is meshed on the surface of a substrate with a porous structure, and the surface of the silicone oil-polydimethylsiloxane gel layer has a continuous silicone oil lubricating layer.
[0007] Furthermore, the silicone oil-polydimethylsiloxane gel layer is obtained by mixing polydimethylsiloxane and silicone oil in a ratio of 1:2.2.
[0008] Furthermore, the substrate surface is a periodically arrayed micrometer-scale pore structure, a submicrometer periodic stripe structure around the micrometer-scale pore structure, and a micro-nanometer deposit recast by metal melting around the micrometer-scale pore structure.
[0009] Furthermore, the maximum aspect ratio of the micrometer-scale pore structure is 6.
[0010] Furthermore, the substrate surface with a porous structure is prepared by femtosecond laser.
[0011] The present invention also provides the use of the above-mentioned self-lubricating anti-coagulation coating in an ECMO centrifugal pump, and prepares the self-lubricating anti-coagulation coating on the surface of the ECMO centrifugal pump.
[0012] The present invention also provides an ECMO centrifugal pump, the surface of the ECMO centrifugal pump body is provided with the above-mentioned self-lubricating anti-coagulation coating, the thickness of the self-lubricating anti-coagulation coating is 0.5 mm, and the surface roughness of the ECMO centrifugal pump body is Ra0.2.
[0013] Furthermore, the ECMO centrifugal pump body is made of stainless steel and prepared using 3D printing technology, and the ECMO centrifugal pump is driven by magnetic coupling.
[0014] The present invention also provides a method for preparing the above-mentioned ECMO centrifugal pump, and the specific steps are as follows: Use femtosecond laser to construct a porous structure on the surface of ECMO centrifugal pump body; Polydimethylsiloxane (PDMS) and silicone oil were mixed in a ratio of 1:2.2 to obtain S-PDMS gel.
[0015] A layer of S-PDMS gel is coated on the porous structure on the surface of the ECMO centrifugal pump body, and UV curing is performed under vacuum conditions, so that the S-PDMS gel layer meshes with the porous structure on the surface of the ECMO centrifugal pump body to obtain a structural precursor; The structural precursor was immersed in silicone oil with a viscosity of 10 mPa.s for two days to obtain an ECMO centrifugal pump with a self-lubricating anti-coagulation coating.
[0016] Furthermore, the UV curing is specifically heating under 80°C UV lamp conditions for 1.5 hours.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: The present invention provides a self-lubricating anticoagulant surface coating, comprising a silicone oil-polydimethylsiloxane gel layer, the silicone oil-polydimethylsiloxane gel layer is meshed on the surface of a substrate with a porous structure, and the surface of the silicone oil-polydimethylsiloxane gel layer has a continuous silicone oil lubricating layer. The silicone oil lubricating layer on the coating surface significantly reduces the shear force during blood flow, thereby reducing the collision and friction damage of blood cells (such as red blood cells, white blood cells and platelets). This effect of reducing damage helps to reduce the risk of hemolysis, that is, the phenomenon that hemoglobin released by the rupture of red blood cells enters the blood. The coating material has good anticoagulant properties, can reduce the adhesion and activation of platelets and fibrinogen, thereby reducing the risk of thrombosis, and the improvement of anticoagulant properties helps to extend the use time of blood in an extracorporeal circulation system, while reducing interference with the coagulation system in the patient's body. The coating material has antibacterial properties and can inhibit the growth and reproduction of bacteria on the surface of the material, which is of great significance for reducing the risk of infection during medical treatment, especially in patients who require long-term extracorporeal circulation support. The self-lubricating anti-coagulation surface coating of the present invention has self-repairing properties and can repair minor damages on the coating surface to a certain extent, thereby maintaining the integrity and performance of the coating. This self-repairing property helps to extend the service life of the coating and reduce the problem of decreased blood compatibility caused by coating damage.
[0018] The present invention provides an ECMO centrifugal pump, on the surface of the ECMO centrifugal pump body, a self-lubricating anticoagulant surface coating is prepared, the surface roughness of the pump body is significantly reduced, and the degree of damage to blood cells by the centrifugal pump in the process of pumping blood is significantly reduced. This helps to reduce the risk of hemolysis and thrombosis, and improve the treatment effect and safety of patients. The self-lubricating anticoagulant surface coating of the present invention has good anticoagulant properties, which can reduce the adhesion and activation of platelets and fibrinogen on the surface of the pump body, thereby reducing the risk of thrombosis. The improvement of blood compatibility enables the centrifugal pump to maintain the fluidity of blood during long-term operation, reducing equipment failures and patient risks caused by coagulation. The smoothness of the surface of the self-lubricating anticoagulant surface coating of the present invention reduces the resistance during blood flow, so that the pump body can extract blood and transport it back to the body with higher efficiency. This helps to meet the patient's demand for blood flow in the body, while reducing energy consumption and blood loss during extracorporeal circulation. Since the self-lubricating anticoagulant coating has excellent wear resistance and corrosion resistance, it can protect the surface of the pump body of the centrifugal pump from erosion by blood and other corrosive substances, which helps to extend the service life of the equipment and reduce downtime and maintenance costs caused by equipment failure. The self-lubricating and anticoagulant properties of the self-lubricating anticoagulant surface coating of the present invention help to reduce the retention and accumulation of blood on the surface of the pump body, thereby reducing the risk of infection. In addition, the stability and reliability of the self-lubricating anticoagulant surface coating of the present invention also help to ensure the normal operation of the centrifugal pump in emergency situations, providing timely and effective treatment support for patients.
[0019] The present invention uses femtosecond laser to prepare a self-lubricating anti-coagulation surface coating, which can accurately control the micro-nano structure of the coating surface, thereby optimizing its self-lubricating and anti-coagulation properties. This precise control helps to meet the requirements for coating performance in different application scenarios. By mixing polydimethylsiloxane (PDMS) with silicone oil to obtain S-PDMS gel, and coating it on the porous structure on the surface of the pump body, a stable coating structure can be formed. This stable coating structure helps to extend the service life of the coating and reduce the performance degradation problem caused by coating shedding. The preparation method is relatively simple and easy to achieve industrial production. This helps to reduce production costs, improve production efficiency, and meet the needs of large-scale clinical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is the testing process of stainless steel-based SLACS; Figure 2The preparation process of stainless steel-based SLACS, in which A. firstly, a porous structure is ablated on the surface of 316 stainless steel using a femtosecond laser Bessel beam, and S-PDMS is fixed on the porous substrate by physical adhesion and chemical bonding. After the subsequent static state, a layer of lubricating fluid is secreted on the surface of SLACS; B. The stainless steel surface after laser ablation; C. The deep hole structure formed by the femtosecond laser pulse train; The chimeric structure formed between DS-PDMS and the porous structure; Figure 3 Detailed schematic diagram of stainless steel-based SLACS; Figure 4 Computer simulation process of stainless steel blood pump processed by SLACS, including A. AFM detection of material physical property roughness; B. Fluid dynamics (CFD) simulation of flow field of blood pump under different roughness; C. As roughness increases, shear stress on the surface of blood pump increases; Figure 5 Anti-adhesion and antibacterial test of stainless steel blood pumps treated with SLACS, including A. blood sliding test; B. platelet adsorption test; C. bacterial adhesion test; D&E Escherichia coli and Staphylococcus aureus antibacterial statistical chart; Figure 6 Cytotoxicity test of stainless steel blood pump treated with SLACS, where A. SLACS has no obvious cytotoxic effect on human umbilical vein endothelial cells; B. SLACS has no obvious cytotoxic effect on rat cardiac microvascular endothelial cells; Figure 7 Schematic diagram of the dynamic experimental mode of the stainless steel blood pump processed by SLACS; Figure 8 The results of blood routine tester, including: A. Dynamic changes of red blood cell count (RBC) in blood at 0h, 0.5h, 1h, 1.5h and 2h; B. Dynamic changes of hemoglobin content in blood at 0h, 0.5h, 1h, 1.5h and 2h; C. Dynamic changes of mean hemoglobin concentration of red blood cells in blood at 0h, 0.5h, 1h, 1.5h and 2h; Fig. 9 These are the results of six coagulation tests, including: A. dynamic changes of thrombin time (PT) in the blood at 0h, 0.5h, 1h, 1.5h and 2h; B. dynamic changes of prothrombin activity (PTA) in the blood at 0h, 0.5h, 1h, 1.5h and 2h; C. dynamic changes of prothrombin time (TT) in the blood at 0h, 0.5h, 1h, 1.5h and 2h; D. dynamic changes of fibrinogen (FIB) in the blood at 0h, 0.5h, 1h, 1.5h and 2h; E. dynamic changes of fibrin degradation products (FDP) in the blood at 0h, 0.5h, 1h, 1.5h and 2h.
[0021] Fig.10 The present invention discloses a process of using an ECMO centrifugal pump modified with the self-lubricating anti-coagulation coating of the present invention. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0023] The present invention is an improvement of a surface coating, and particularly relates to a blood pump. According to the bionic characteristics, improvements are made on the basis of traditional stainless steel materials, and a self-lubricating anti-coagulation surface coating is prepared by bionic lotus leaves, fish scales, and pitcher plants using femtosecond lasers to improve the blood compatibility of the surface of medical materials. The micro-nano structure and the chemical treatment are adjusted to make it have antibacterial and anti-adhesion properties and reduce hemolysis. Hemolysis and thrombosis during extracorporeal blood circulation are effectively reduced, so that the material has good self-repairing properties, liquid repellency, and blood compatibility.
[0024] like Figure 2 As shown in A, the present invention is inspired by the secretion of cardiac endothelial cells, and a self-lubricating anti-coagulation coating (SLACS) composed of silicone oil-polydimethylsiloxane gel (S-PDMS gel) is prepared on a porous stainless steel substrate. The coating is used to improve the ECMO centrifugal pump body, such as Figure 1 As shown, the specific steps are as follows: Step 1: A porous structure with a high aspect ratio is formed on the surface of a 16 stainless steel substrate by ablating a femtosecond laser pulse train in a Burst mode and a spatially shaped Bessel beam, thereby obtaining a porous substrate.
[0025] Step 2: treating the porous substrate with oxygen plasma, and wrapping the porous substrate with S-PDMS gel; Step 3: Immerse the porous substrate coated with the S-PDMS gel in low-viscosity silicone oil. After standing, a lubricating liquid layer is secreted from the surface of the S-PDMS gel, thereby obtaining a self-lubricating anti-coagulation surface coating on the porous substrate.
[0026] like Figure 2 As shown in Figure B, the present invention uses a femtosecond laser to ablate a hole structure with rich nanoparticles on the stainless steel surface at a spacing of 6μm. At the same time, the burst laser mode allows up to 250 laser pulse trains to repeatedly ablate the same micropore, further increasing the aspect ratio of the micropore. Observing the cross-sectional structure of SLACS, the treated porous substrate forms a stable physical and chemical bond with the S-PDMS covered thereon, and an interlaced meshing is formed between the S-PDMS and the porous structure. At the same time, the microporous structure can reach a depth of about 10μm ( Figure 2 D).
[0027] like Figure 3As shown in Figure 2, the burst mode femtosecond laser pulse train ablates the surface of 316L stainless steel to form an irregular micro-nano composite structure. The micron-scale structure is mainly composed of 6μm×6 μm The porous structure is composed of periodic arrays. Due to thermal effects and ultrafast laser nonlinear ablation, the porous structure has an irregular shape and is roughly elliptical, with a long axis of about 3.3μm and a short axis of about 2.5μm. From the cross-section, the ablation holes twist and extend downward from the metal surface, with a depth of about 15μm and a maximum depth-to-diameter ratio of about 6. There are submicron periodic stripe structures (laser-induced periodic surface structure LIPSS) with a consistent direction close to the laser wavelength and micro-nano deposits recast by metal melting around the micron-sized ablation holes.
[0028] The present invention provides an ECMO centrifugal pump, whose stainless steel pump body is prepared by using selective laser melting 3D printing technology, and its surface roughness is Ra6.3. After the stainless steel pump body is treated by oxygen plasma, S-PDMS is covered on its surface to form a stable and uniform self-lubricating anti-coagulation surface coating on the surface of the stainless steel pump body.
[0029] A self-lubricating anti-coagulation surface coating with a thickness of 0.5 mm is formed on the surface of the stainless steel pump body. The surface roughness of the stainless steel pump body with the self-lubricating anti-coagulation surface coating is Ra0.2.
[0030] Preferably, the stainless steel pump body is prepared by using the porous substrate having a self-lubricating anti-coagulation surface coating obtained by the above preparation method.
[0031] Preferably, the ECMO centrifugal pump is driven by magnetic coupling to avoid additional hemolysis caused by the rotating shaft.
[0032] Example 1 like Fig.10 As shown, medical stainless steel is a common material for preparing blood-contact centrifugal pumps and is widely used in clinical applications. 316L stainless steel is selected as the substrate of SLACS. The present invention improves the coating of the ECMO centrifugal pump head by SLACS, and the specific steps are as follows: Step 1: Prepare a stainless steel blood pump A stainless steel blood pump was prepared by 3D printing technology. The blood pump was driven by magnetic coupling and had a surface roughness of 6.3. A femtosecond laser (FemtoYL-20, YSLP-photonics, Wuhan, China) was used to construct a three-dimensional porous structure on the surface of the stainless steel blood pump to obtain a porous stainless steel blood pump with an irregular micro-nano composite structure on the surface.
[0033] Step 2: Preparation of S-PDMS gel Polydimethylsiloxane PDMS (precursor and curing agent mixed at a ratio of 10:1, DC-184, Dow Corning) and silicone oil (Aladdin, PMX-200, viscosity = 350 mPa.s) were mixed at a ratio of 1:2.2 to obtain S-PDMS gel.
[0034] Step 3, treating the surface of the porous stainless steel blood pump with oxygen plasma, and wrapping the surface of the porous stainless steel blood pump with S-PDMS gel; After the surface porous stainless steel blood pump was treated with oxygen plasma, a layer of S-PDMS gel was coated on its surface and heated for 1.5 hours under vacuum and 80°C ultraviolet lamp conditions. A firmly adhered S-PDMS gel layer was formed on the surface of the surface porous stainless steel blood pump.
[0035] Step 4: Improving the storage property of the S-PDMS gel layer; The surface porous stainless steel blood pump with an S-PDMS gel layer adhered to the surface was immersed in low viscosity silicone oil (Aladdin, PMX-200, viscosity = 10 mPa.s) for 2 days to obtain a stainless steel blood pump with a self-lubricating anticoagulation coating (SLACS) with a thickness of 0.5 mm.
[0036] Step 5: The blank control group 3D printed pump body was not treated after cleaning, and the structural errors of the two pumps were both ±1%.
[0037] The feasibility of this technology as a surface modification technology for ECMO centrifugal pumps was further verified through static experiments, simulations, and dynamic experiments, providing a new option for future safe medical treatment, as follows: 1. Computer simulation of hemolysis in stainless steel blood pumps treated with SLACS like Figure 4 As shown in A, the surface roughness of the stainless steel pump body is Ra6.3, and the roughness of SLACS is Ra0.2. The self-lubricating layer formed by SLACS reduces the surface roughness. Figure 4 As shown in B, computational fluid dynamics (CFD) is used to simulate the flow field of the blood pump and analyze factors such as shear stress, pressure, speed, and force in the blood pump flow field. Figure 4 As shown in Figure C, as the roughness decreases, the shear stress on the blood pump surface decreases. Therefore, the stainless steel blood pump treated with SLACS reduces the damage to red blood cells and can better avoid hemolysis.
[0038] 2. Anti-adhesion and antibacterial test of stainless steel blood pump treated with SLACS like Figure 5As shown in Figure A, when fresh blood slides off the SLACS, almost no residue is left. In contrast, blood flows slowly on the stainless steel surface, leaving obvious movement traces. The sliding properties of the SLACS self-lubricating surface provide the basic conditions for its anti-adhesion effect. Figure 5 As shown in Figure B, SLACS reduced the release of platelet factor 4 (PF4) compared with stainless steel, with a significant difference (P < 0.05, n = 3), which indicates that SLACS reduced platelet adhesion and reduced the degree of platelet activation. Figure 5 C. The super-slippery properties of SLACS effectively reduce Escherichia coli ( Figure 5 D, P < 0.05, n = 3) and Staphylococcus aureus ( Figure 5 E, P < 0.05, n = 3) adhesion on the pump surface. Therefore, SLACS has good antibacterial properties and can effectively reduce possible infections during application.
[0039] 3. Cytotoxicity test of stainless steel blood pumps treated with SLACS Human umbilical vein endothelial cells (HUVECS) were used Figure 6 A) and rat cardiac microvascular endothelial cells (RCMEC) ( Figure 6 B) Perform CCK8 experiment. Figure 6 As shown, there was no significant change in cell viability. SLACS had no significant cytotoxic effect on human umbilical vein endothelial cells and rat cardiac microvascular endothelial cells. The research results of the present invention show that SLACS has passed the cytotoxicity test of medical biomaterials, has preliminary biosafety, has good biocompatibility, and is a reliable basis for the next stage of testing.
[0040] 4. Anti-hemolysis and anticoagulation test of stainless steel blood pumps treated with SLACS under dynamic conditions Dynamic experimental mode diagram Figure 7 As shown, a circulation loop was constructed. The blood volume of the two loops was equal, and the blood flow difference was ±5%. The flow rate of the stainless steel pump was 0.77 L / min and the speed was 2010 rpm. The flow rate of the stainless steel blood pump treated by SLACS was 0.72 L / min and the speed was 2097 rpm. The number of red blood cells (RBC) was detected by a blood routine detector at 0 hours, 0.5 hours, 1 hour, 1.5 hours and 2 hours ( Figure 7 A) Hemoglobin content (HGB) Figure 7 B) and the mean hemoglobin concentration (MCHC) in red blood cells ( Figure 7C). However, at 1.5 hours, the number of red blood cells in both groups decreased compared with 0 hours. However, the number of red blood cells in the SLACS-treated stainless steel blood pump was higher than that in the stainless steel blood pump, indicating that the SLACS-treated stainless steel blood pump caused less damage to red blood cells, which is consistent with previous results. In addition to the red blood cell count, free hemoglobin in plasma is an important product of hemolysis. At 1.5 hours, the HGB and MCHC of the stainless steel blood pump were lower than those of the SLACS-treated stainless steel blood pump, but there was no statistical significance (P>0.05, n=3). Therefore, the SLACS-treated stainless steel blood pump caused less damage to red blood cells than the stainless steel blood pump. Hemolysis (i.e., red blood cell destruction) may be caused by factors such as substances released from the material, the gas-blood interface, shear force, and complement components. Usually, EDTA-Na is used as an anticoagulant for routine blood tests, but sodium citrate was used in this experiment. Although the test can be performed, this may be the reason for the unclear results.
[0041] Figure 8 As shown, the thrombin time (PT) in the blood was measured by an automatic coagulation analyzer at 0, 0.5, 1, 1.5, and 2 hours ( Figure 8 A) Thrombin activity ( Figure 8 B) Activated partial thromboplastin time (APTT) ( Figure 8 C) and fibrinogen (FIB) ( Figure 8 D). Control group (intrinsic group): The thrombin time (PT), thrombin activity, activated partial thromboplastin time (APTT) and fibrinogen (FIB) in the blood were measured at 0 hours, 0.5 hours, 1 hour, 1.5 hours and 2 hours under the condition of stainless steel material without coating treatment. The present invention observed whether the SLACS-treated stainless steel blood pump caused accelerated coagulation in dynamic circulation.
[0042] Prothrombin time (PT) is the time required for blood to coagulate in vitro by artificially simulating the exogenous coagulation mechanism. It reflects the exogenous coagulation function and is clinically used to assess whether patients have coagulation disorders or bleeding disorders. In the coagulation test, the coagulation contact time of blood and biomaterials changes, and a longer prothrombin time generally indicates less coagulation. The prothrombin time of the coating group was longer than that of the endogenous group, indicating that SLACS has a better anticoagulant effect, but the difference is not significant ( Fig. 9 A). Prothrombin activity (PTA) is related to prothrombin time. As an indicator of standardized PT, PTA mainly reflects the level of exogenous and common pathway coagulation factors in patients. Compared with normal people, PTA is more sensitive to factor 7. The decrease in PTA indicates that the consumption of factor 7 is more obvious. The prothrombin activity PTA of the coating group was lower than that of the control group, and the difference was obvious at 1-1.5 hours ( Fig. 9 B).
[0043] The activated partial thromboplastin time (APTT) is an indicator of blood coagulation function, which reflects the intrinsic coagulation pathway. In dynamic experiments, APTT is a more effective indicator for the application of anticoagulant drugs. The APTT of the control group was always higher than that of the stainless steel blood pump treated with SLACS at 0 hours, 0.5 hours, 1 hour, 1.5 hours and 2 hours, and was significantly higher at 2 hours ( Fig. 9 C). Fibrinogen deficiency (less than 100 mg / dL), fibrinogen activation, elevated levels of fibrin degradation products, or heparin can prolong the thrombin time. Fibrinogen is the main protein involved in blood coagulation. During the coagulation process, fibrinogen is hydrolyzed by thrombin to release fibrin degradation products (FDP). In addition, to a certain extent, it indicates that there is a high fibrinolytic state in the coagulation process and that the coagulation raw materials are exhausted during the coagulation process. This may be due to the fact that the use of anticoagulants in in vitro dynamic experiments cannot fully simulate the use of anticoagulants in circulating blood in vivo. However, the SLACS-treated stainless steel blood pump is not inferior to the stainless steel blood pump in terms of resistance to red blood cell damage and has better anticoagulant properties. To a certain extent, it can be seen that the SLACS-treated stainless steel blood pump has a better application effect.
[0044] in conclusion Inspired by the secretion of cardiac endothelial cells, the present invention prepares a self-lubricating anti-coagulation coating SLACS composed of silicone oil-polydimethylsiloxane gel on a porous stainless steel substrate. Static experiments show that SLACS has good resistance to blood adhesion, blood cell adhesion, low hemolysis and low biological toxicity. Furthermore, SLACS is used to modify the blood contact surface of a stainless steel blood pump, and dynamic tests show that the modified blood pump has lower procoagulant properties, which further verifies the feasibility of the SLACS material of the present invention under dynamic conditions. Therefore, the self-lubricating anti-coagulation surface prepared by the present invention can be used for the modification of blood pumps for short-term use.
[0045] Compared with traditional materials, SLACS is prepared on the surface of the ECMO centrifugal pump body of the present invention. SLACS has self-healing properties to ensure the integrity of the coating under circulation. The self-lubricating anti-coagulation surface coating significantly improves the lyophobicity. If the nickel-titanium alloy material of the traditional ECMO centrifugal pump is used for a long time, its working process will be in contact with the blood for a long time, which is easy to cause material adhesion. The improvement of lyophobicity effectively reduces the basis for adhesion and effectively separates the material from the blood. On the basis of lyophobicity, the present invention adjusts the chemical treatment to have good antibacterial and blood compatibility. The material improves anticoagulability, reduces hemolysis and platelet and fibrinogen adhesion and activation. In vivo experiments show that hemolysis and thrombosis in in vivo blood applications are effectively reduced. The self-lubricating anti-coagulation surface coating is intended to enable medical materials to obtain better blood compatibility. The present invention is only applicable to blood application materials.
[0046] The use of femtosecond laser to prepare self-lubricating anticoagulant surface coatings can improve the blood compatibility of medical material surfaces. The micro-nano structure and the adjustment of chemical treatment make it have antibacterial and anti-adhesion properties and reduce hemolysis. It effectively reduces hemolysis and thrombosis during extracorporeal blood circulation. The SLACS of the present invention not only has excellent biocompatibility and anticoagulant properties, but also needs to be able to withstand the mechanical and chemical stresses during the operation of the ECMO instrument, ensuring the safety of patients and the treatment effect.
[0047] In summary, the present invention solves the damage of ECMO centrifugal pump flow shear to blood cells and reduces hemolysis and thrombosis caused by collision and friction damage of blood cells, aiming to further improve the blood compatibility of medical materials. It is expected to improve multiple key blood parameters such as antibacterial and anticoagulant properties of the materials through simulated in vivo experimental research.
Claims
1. A self-lubricating anticoagulant coating, characterized in that: The invention comprises a silicone oil-polydimethylsiloxane gel layer, which is meshed on the surface of a substrate with a porous structure and has a continuous silicone oil lubricating layer on the surface of the silicone oil-polydimethylsiloxane gel layer.
2. A self-lubricating anti-coagulation coating according to claim 1, characterized in that: The silicone oil-polydimethylsiloxane gel layer is obtained by mixing polydimethylsiloxane and silicone oil in a ratio of 1:2.
2.
3. The self-lubricating anti-coagulation coating according to claim 1, characterized in that: The substrate surface comprises a periodically arrayed micrometer-scale pore structure, a submicrometer periodic stripe structure around the micrometer-scale pore structure, and a micro-nanometer deposit recast by metal melting around the micrometer-scale pore structure.
4. A self-lubricating anti-coagulation coating according to claim 3, characterized in that: The maximum aspect ratio of the micron-scale pore structure is 6.
5. The self-lubricating anti-coagulation coating according to claim 3, characterized in that: The substrate surface with the porous structure is prepared by using femtosecond laser.
6. Use of the self-lubricating anticoagulant coating according to any one of claims 1 to 5 in an ECMO centrifugal pump, characterized in that: Preparation of self-lubricating anticoagulant coating on the surface of ECMO centrifugal pump.
7. An ECMO centrifugal pump, characterized in that: The surface of the ECMO centrifugal pump body is provided with a self-lubricating anti-coagulation coating according to any one of claims 1 to 5, the thickness of the self-lubricating anti-coagulation coating is 0.5 mm, and the surface roughness of the ECMO centrifugal pump body is Ra0.
2.
8. An ECMO centrifugal pump according to claim 7, characterized in that: The ECMO centrifugal pump body is made of stainless steel and is prepared using 3D printing technology. The ECMO centrifugal pump is driven by magnetic coupling.
9. A method for preparing an ECMO centrifugal pump according to claim 7 or 8, characterized in that: The specific steps are as follows: Use femtosecond laser to construct a porous structure on the surface of ECMO centrifugal pump body; The polydimethylsiloxane (PDMS) and silicone oil were mixed in a ratio of 1:2.2 to obtain S-PDMS gel; A layer of S-PDMS gel is coated on the porous structure on the surface of the ECMO centrifugal pump body, and UV curing is performed under vacuum conditions, so that the S-PDMS gel layer meshes with the porous structure on the surface of the ECMO centrifugal pump body to obtain a structural precursor; The structural precursor was immersed in silicone oil with a viscosity of 10 mPa.s for two days to obtain an ECMO centrifugal pump with a self-lubricating anti-coagulation coating.
10. The method for preparing an ECMO centrifugal pump according to claim 9, characterized in that: The UV curing is specifically heating under 80°C UV lamp for 1.5 hours.